MEASUREMENT OF PUBLIC TRANSPORT ACCESSIBILITY CONDITION AT KOTA BANDA ACEH - Tonny, Judiantono (Jurnal Perencanaan Wilayah dan Kota, 2011)
Kota Banda Aceh with 224.233 peoples at 2007 deserved by 1.012 units of public transportation in any type, it means there are 5,1 seats for each 100 peoples of Kota Banda Aceh. Length of road which deserved by public transport is 45,35 Km, it means only 10,92% length of road in Kota Banda Aceh. For Banda Aceh with wide 61,359 Km2, the coverage of public transport just 15,9%. Any type these accessibility measurement will give us different means the level of public transport accessibility. Through this accessibility level measuring, we will gets some recomendation for public transport policy of Kota Banda Aceh and its implication, as consideration for Public Transport decision maker. Â  Key words : Public Transportation, Accessibility